Worksite Physical Activity Barriers and Facilitators: A Qualitative Study Based on the Transtheoretical Model of Change - Planchard, Jo-Hanna; Corrion, Karine; Lehmann, Lisa; d'Arripe-Longueville, Fabienne (Frontiers in Public Health, 2018)
Background: Many of the studies on worksite physical activity (PA) have investigated either the effectiveness of PA programs for employees and the work-related outcomes or health promotion interventions to increase PA. However, studies on barriers and enabling factors for participation are scarce and have generally not been theoretically grounded. The purpose of this qualitative study was to identify worksite PA barriers and facilitators from the perspective of the transtheoretical model of change (TTM). Methods: Thirty employees (15 females and 15 males; Mage = 44.70; SD = 5.20) were recruited to participate in semi-structured interviews lasting from 60 to 90 min. Participants came from several organizations that offered PA programs and were at different exercise stages of change. They were invited to describe: (a) general information on the place of PA in their daily lives and in the workplace, and the reasons for (b) worksite PA participation or (c) non-participation. The interview transcripts were analyzed both inductively and deductively with reference to the exercise stages of change. Results: Three categories of barriers and facilitators related to physical, psychological and environmental dimensions were identified. For all exercise stages of change combined, psychological and environmental barriers were significantly more reported than physical barriers, whereas physical and psychological facilitators were more cited than environmental facilitators. Further qualitative analysis suggested that these categories differed with the exercise stage of change. At the precontemplative and contemplative stages, all types of barriers predominated (e.g., physical constraints due to the workstation, fear of management disapproval, time constraints). At the preparation stage, physical, and psychological needs emerged in relation to worksite PA (e.g., need to compensate for sedentary work, stress regulation). At the action and maintenance levels, physical, psychological, and environmental facilitators were reported (e.g., enhanced physical condition, workplace well-being, social ties). At the relapse stage, specific life changes or events broke the physically active lifestyle dynamics. Conclusion: This study identified the contribution of different types of worksite PA barriers and facilitators according to the exercise stage of change. The identified facilitators are consistent with the general TTM processes of change, while being specific to the workplace. Practical strategies are discussed.